Determination of region-specific data of yield and quality of alternatives to silage maize in fodder crops – field trails with forage gras and clover grass mixtures, Sorghum as well as whole plant silage of grain - Wosnitza, Andrea; Hartmann, Stephan (Julius-Kühn-Archiv, 2014)
This project should generate current regional results over a period of three years about the parameter yield and quality of alternative fodder crops to maize; this includes grass and clover grass mixtures, silage maize, varieties of Sorghum/millets and whole plant silages of wheat, rye and triticale. The tested silage maize showed the highest and most reliable average dry matter yield with 23 tons per hectare, with a very low variance. The Sorghum and millet varieties had dry matter yields of 3 to 5 tons per hectare below the silage maize yield but with individual values fluctuating in a broad range within years and locations. With values far below 28% the dry matter contents were not suitable for ensiling. The grass and clover grass mixtures are good, stable and established alternatives to maize for silage. They achieved high yields comparable with these of Sorghum but stable and with a highly suitable dry matter content for ensiling. The yield of the whole plant silages was up to 22% lower compared with maize. So none of the alternative crops can compete with the high level yield of silage maize in its favoured region, therefore would be a combination of two crops recommended. But some individual locally adapted mixtures or varieties of the alternative crops reached nearly 80% of the maize yield. Silage maize showed the highest level of the net energy content for lactation (NEL), followed by the values of the fodder crops and the whole plant silages. The Sorghum varieties showed the lowest NEL value of all tested cultures. The highest crude protein showed the fodder crops contents. Silage maize, Sorghum and the whole plant silages had values lying nearly around the 50% mark of the fodder crops.